2001
DOI: 10.1016/s0378-1097(01)00265-8
|View full text |Cite
|
Sign up to set email alerts
|

A physical map of the megaplasmid pHG1, one of three genomic replicons in Ralstonia eutropha H16

Abstract: We have used pulsed field gel electrophoresis and megabase DNA techniques to investigate the basic genomic organization of Ralstonia eutropha H16, and to construct a physical map of its indigenous megaplasmid pHG1. This Gram-negative, soil-dwelling bacterium is a facultative chemolithoautotroph and a denitrifier. In the absence of organic substrates it can grow on H 2 as its sole energy source and CO 2 as its sole source of carbon. Under anaerobic conditions it can utilize nitrate as a terminal electron accept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 14 publications
0
6
0
2
Order By: Relevance
“…The arrangement of aceB in the chromosome of R. eutropha HF39 is very similar to that of R. metallidurans CH34. It is well demonstrated that R. eutropha H16 contains two circular chromosomes with sizes of 4.1 and 2.9 Mb in addition to a 0.44‐Mb conjugative megaplasmid pHG1 [17]. Since R. eutropha HF39Δ aceB1 could still grow on acetate (Fig.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The arrangement of aceB in the chromosome of R. eutropha HF39 is very similar to that of R. metallidurans CH34. It is well demonstrated that R. eutropha H16 contains two circular chromosomes with sizes of 4.1 and 2.9 Mb in addition to a 0.44‐Mb conjugative megaplasmid pHG1 [17]. Since R. eutropha HF39Δ aceB1 could still grow on acetate (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…ncbi.nlm.nih.gov/PMGifs/Genomes/eub_g.html), R. metallidurans CH34 (http://genome.ornl.gov/microbial/reut/) and S. cerevisiae (http://genome-www.stanford.edu/Saccharomyces/), two ICL isoenzymes were also found in R. eutropha HF39 in this study. Their arrangement on the three replicons [17] is di¡erent from that of aceA1 or aceA2 in R. metallidurans CH34, indicating that there are di¡erences in the organization of genes in these phylogenetically related bacteria. In R. eutropha HF39, it is obvious that only ICL1 is speci¢c to glyoxylate cycle since only R. eutropha HF39vaceA1 failed to grow on acetate (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…It is interesting to compare this situation with the genome organization of the soil‐dwelling hydrogenotroph R. eutropha H16. In this bacterium, pulse field electrophoresis studies have indeed shown the presence of two major replicons of 4.1 Mb and 2.9 Mb, and of a 0.44‐Mb megaplasmid that contains the genetic determinants for hydrogenotrophy and enables anaerobic growth at the expense of nitrate [90]. These genetic determinants are chromosome‐encoded in R. metallidurans CH34 as they are present in the plasmid‐free derivative of R. metallidurans CH34 [2,16].…”
Section: Genomics Of the Genus Ralstoniamentioning
confidence: 99%
“…Conjugational mapping using two different conjugative plasmids (pULB113, an RP4::miniMu derivative, and pMOL50, a derivative of pMOL28) able to mobilize chromosomal determinants showed that these determinants are linked to other housekeeping gene determinants on the chromosome [16]. It is not yet known if the genome of R. metallidurans contains a structure like the megaplasmid of R. solanacearum, or more generally two major replicons as is the case for both R. solanacearum G1000 and R. eutropha H16 [88,90]. Strain CH34 contains two large plasmids of 180 and ∼250 kb [14,75] that are especially rich in metal resistance genes and in open reading frames (ORFs) similar to well‐known metal resistance genes.…”
Section: Genomics Of the Genus Ralstoniamentioning
confidence: 99%
“…In the case of strain CH34, the taxonomic classification changed from Alcaligenes via Ralstonia and Wautersia into the genus Cupriavidus (Makkar and Casida 1987) and seems to be stabilized now Vandamme and Coenye 2004;Vaneechoutte et al 2004;Chen et al 2001). However, older or different genus or species names are still used, for instance in the recent papers on the catabolic strain JMP134 or the reference chemolithoautotrophic strain H16 (Schwartz and Friedrich 2001;Pohlmann et al 2006;Fricke et al 2009). …”
Section: The Shaping Of Cupriavidus Metalliduransmentioning
confidence: 99%